Where value creation meets appreciation and care: motives of farmers for direct marketing in Brandenburg, Germany - Suse Brettin (Sustainability: Science, Practice, & Policy)
In recent years, the number of agricultural enterprises engaged in various forms of direct marketing has increased, both internationally and in Germany. To date, however, little is known about the farmers’ motives for selling their products directly to consumers. This knowledge gap seems particularly striking in light of the sociopolitical objective of fostering this mode of marketing and distribution. Given the hegemonic conceptualization of the farmer as a rational choice entrepreneur, the reasons for this could be purely economic, or a response to a seemingly growing demand for local produce. Nonetheless, the little research that exists on farmers’ motivations also points in other directions and emphasizes the importance of relationality and socioecological embeddedness, which are central characteristics of care. This article thus explores how logics of care provide a starting point for farmers’ motivation to direct marketing. Through the analysis of nine qualitative interviews with farmers in Brandenburg, Germany, who sell some or all of their products directly, it illustrates how they consider themselves within a structure of multifaceted responsibilities. The results further indicate that direct marketing seems to be a logical consequence of these responsibilities. By providing a more nuanced picture, the direct selling of produce can be seen as both a strategy for value creation and a means of appreciation and a set of practices of care toward the complex web of human and non-human beings contributing to agricultural production.